Response of Sugarcane Setts to Bio-Stimulant Solutions at Tillering Stage - Oñal, Jr., Paulino A; Andrade, Francis E.; Jayme, Glen R.; Montorio, John Edcelest O. (Future Science / FSH-PH Publications, 2024)
The study aims to determine the response of sugarcane setts to the different level of concentrations bio-stimulant solutions (BSS) that can accelerate the rooting and tillering. The study was conducted at UNO-R School of Agriculture, Philippines from October 15, 2023 -January 15, 2024. Phil 99-1793 variety is used. It was laid out in Completely Randomized Design with 4 treatments, replicated 4 times. The treatments were; no BSS (control), 200ml, 300ml, and 400ml BSS. Cane setts were prepared a day before planting. Leaf sheaths were remove and viable eye buds was selected. Setts were soaked in water for 24 hours and air-dried for 30 minutes before planting. The BSS were diluted in water before application. It was applied at plant base 15, 45, and 75 days after planting (DAP). Statistical analysis revealed highly significant on root weight and length with 110grams and 100.33cm for 400ml BSS, respectively. Great significant result also was observe for the tiller height at 30DAP and 60DAP with 26.10cm and 43.08cm respectively for 400ml BSS treatment. On tiller weight at 90DAP, number of tillers at 30DAP and number nodes at 90DAP statistics indicates a significant result with 752grams, 1.75tillers and 8.10nodes for 400ml BSS treatment. Application of 400ml BSS shorten the germination to only 5.30days while control treatment germinated at 8.03days. Application of 400ml BSS also increases the biomass with 4,310,00kg/hectare higher than the control with 2,242.50 kg/hectare. The study recommends the application of 400ml of BSS to accelerate the rooting and tillering of sugarcane setts up to 90DAP.